Surgical management of traumatic spondylolisthesis of the axis: Kirurško zdravljenje travmatske spondilolisteze 2. vratnega vretenca - Movrin, Igor; Četnik, Andrej (Acta Medico-Biotechnica, 2021)
Purpose: AThe optimal treatment modality for traumatic spondylolisthesis (TSA) of the axis (second cervical vertebra) remains controversial. Many conservative and anterior techniques have been used to treat these injuries.Case report: We describe a 29– year–old woman who presented to the emergency department with severe neck pain after falling down a flight of stairs. Cervical plain radiographs and computer tomography (CT) scan demonstrated a major C2 body anterior dislocation with bilateral C2 pedicle fractures. A Crutchfield extension was applied, with four kilograms of traction initially, with the neck in slight extension. After two hours of traction, plain radiographs showed near–anatomical reduction. The same day the patient underwent an anterior C2/C3 discectomy and autologous bone fusion with a cervical spine locking plate (CSLP). There were no neurological deficits postoperatively and the patient was asymptomatic. She was discharged home on postoperative day eight with a Philadelphia collar for 6 weeks.Conclusion: Anterior C2/C3 discectomy and fusion may be feasible and safe in unstable TSA, with the benefit of high primary stability, anatomical reduction, a high union rate, and favorable clinical outcome
Keywords: axis; traumatic spondylolisthesis; Hangman's fracture; anterior cervical spine fusion